2021
DOI: 10.1159/000511911
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of α1-Adrenergic Receptor-Induced Increased Contraction of Rat Mesenteric Artery in Aging Hypertension Rats

Abstract: Introduction: Vasoconstriction is triggered by an increase in intracellular-free calcium concentration. Growing evidence indicates that contraction is also regulated by calcium-independent mechanisms involving RhoA-Rho kinase (ROCK), protein kinase C (PKC), and so on. In this study, we studied the changes of vascular reactivity as well as the underlying signaling pathways in aging spontaneously hypertensive rats (SHRs). Methods: The artery tension induced by α1-adrenergic receptor activator (α1-AR) phenylephri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 49 publications
2
12
1
Order By: Relevance
“…As shown in Figure 1 , Emax was significantly increased in SHR compared with WKY rats ( p <0.01); Emax was significantly increased in OldSHR compared with OldWKY rats ( p <0.01). This experiment showed that the mesenteric vessels from hypertension are more sensitive to High K + in hypertension, which is consistent with other reports ( Wei et al, 2021 ; Cui et al, 2022 ).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…As shown in Figure 1 , Emax was significantly increased in SHR compared with WKY rats ( p <0.01); Emax was significantly increased in OldSHR compared with OldWKY rats ( p <0.01). This experiment showed that the mesenteric vessels from hypertension are more sensitive to High K + in hypertension, which is consistent with other reports ( Wei et al, 2021 ; Cui et al, 2022 ).…”
Section: Resultssupporting
confidence: 94%
“…The percentage of Emax caused by U-46619 relative to Emax caused by high K + solution (%Emax) was calculated. The vasoconstriction induced by U-46619 was different from those of vascular responses induced by high K + or PE, as previously reported ( Wei et al, 2021 ). The response of mesenteric vessels to U-46619 was significantly increased in hypertension.…”
Section: Resultssupporting
confidence: 78%
“…Several studies confirmed that most arteries in SHRs had increased sympathetic innervation and elevated α1-adrenergic receptor-mediated contractile responses compared to normotensive rats [ 49 ]. The thoracic aorta, as a type of elastic artery, undergoes specific development during hypertension, and the hypertrophied arterial wall displays decreased contractile efficiency as a result of structural remodeling along with increased sensitivity of adrenergic receptors [ 11 ].…”
Section: Discussionmentioning
confidence: 98%
“…2018) and α 1 ‐adrenoceptor‐induced (Wei et al . 2021) arterial tone. Similar to the discrepancy in rat studies, investigations of mouse small mesenteric arteries demonstrated an inconsistent impact of ageing on L‐type channel expression and function (del Corsso et al .…”
Section: Ageing and Smooth Muscle Ca2+ Handlingmentioning
confidence: 99%
“…An enhanced myogenic tone without a change in SMC [Ca 2+ ] i at high intravascular pressure suggested an increase in SMC Ca 2+ sensitivity in middle cerebral arteries with intact endothelium from old rats (Geary & Buchholz 2003). Later studies in mouse and rat mesenteric artery implicated increased Rho kinase activity in the age-dependent increase in vascular SMC Ca 2+ sensitivity resulting in an augmentation of myogenic (Björling et al 2018) and α 1 -adrenoceptor-induced (Wei et al 2021) arterial tone. Similar to the discrepancy in rat studies, investigations of mouse small mesenteric arteries demonstrated an inconsistent impact of ageing on L-type channel expression and function (del Corsso et al 2006;DuPont et al 2016;Mikkelsen et al 2016).…”
Section: Role Of Voltage-gated Ca 2+ (L- T-type) Channelsmentioning
confidence: 99%